Needs Assessment for Effective Development in the Rural Areas of the Niger Delta Region, Nigeria - Sibiri, Elliot A.; Uzobo, Endurance (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
The lack of needs assessment is the leading cause of ineffective and uneven development in rural areas. Previous studies on needs assessment have largely focused on urban development. However, little is known about needs assessment in the rural areas of the Niger Delta Region. This study, therefore, aimed at assessing the developmental needs of rural areas in the Niger Delta Region. A descriptive cross-sectional survey was conducted in three states: Bayelsa, Delta and Rivers State. A total sample of 450 respondents (aged 18-50 years) were randomly selected in 15 rural communities within the selected states, while 15 focus group discussions and 30 in-depth interviews were conducted among the residents to complement the quantitative data. A structured and pre-tested questionnaire and interview guides were used as methods of data collection. Descriptive statistics and content analysis were used as analytic strategies respectively. Although findings showed that majority of the rural dwellers in Rivers, Delta and Bayelsa States were faced with the challenges of flooding, poor educational facilities, poverty/unemployment, poor medical facilities, poor/electricity supply and poor communication network; the provisions of portable water, healthcare facilities, educational facilities, skill acquisition programmes, electricity and business start-up capital were mostly desired by the participants. This study, therefore, has policy implication direction for rural development by stakeholders for effective initiation and implementation of community-based projects in the Niger Delta rural communities. Keywords: Needs assessment, rural development, infrastructure, poverty, Niger Delta Region